2012
DOI: 10.1371/journal.pone.0031305
|View full text |Cite|
|
Sign up to set email alerts
|

Prolactin Secretion in Healthy Adults Is Determined by Gender, Age and Body Mass Index

Abstract: BackgroundProlactin (PRL) secretion is quantifiable as mean, peak and nadir PRL concentrations, degree of irregularity (ApEn, approximate entropy) and spikiness (brief staccato-like fluctuations).HypothesisDistinct PRL dynamics reflect relatively distinct (combinations of) subject variables, such as gender, age, and BMI.LocationClinical Research Unit.SubjectsSeventy-four healthy adults aged 22–77 yr (41 women and 33 men), with BMI 18.3–39.4 kg/m2.MeasuresImmunofluorometric PRL assay of 10-min samples collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
3
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 69 publications
3
61
3
7
Order By: Relevance
“…Results of this study noted a significantly inversely correlation between PRL and the age in whole study population, this finding agree with many studies which found an association between PRL secretion and the age [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…Results of this study noted a significantly inversely correlation between PRL and the age in whole study population, this finding agree with many studies which found an association between PRL secretion and the age [48,49].…”
Section: Discussionsupporting
confidence: 93%
“…Evidence from previous finding considered this observation is consistent with altered (increased) dopaminergic tonus in the elderly during the sleep period (23).Positive correlation was observed between prolactin and LH (R 0.398, p-value 0.002). Similarity to ours, Kazanci, showed that, prolactin potentiates the stimulatory effects of LH on testicular steroidogenesis furthermore prolactin activates leydig cells by increasing their responsiveness to LH (24).…”
supporting
confidence: 87%
“…Peak concentrations of this hormone, which occur shortly prior to the onset of sleep, have been demonstrated to negatively correlate with age [46,47]. This, and reduced pulse amplitude during sleep in older age, indicates decreased dopaminergic inhibitory action on prolactin production in the elderly during the sleep period [15,26].…”
Section: Pituitary: Gh Igf and Prolactinmentioning
confidence: 99%